Analysis of Entertainment Tax Revenues in the City of Bandung Period of Fiscal Year 2014-2018 - et. al., Silviana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study was conducted to analyze the effectiveness of local tax revenues, especially entertainment tax in the city of Bandung. Research period 2014-2018. This type of research is a quantitative descriptive study with a descriptive statistical analysis approach. The results of the analysis show that the average effectiveness of entertainment tax revenue is very effective, but when viewed annually from 2014-2018 the effectiveness of entertainment tax revenue has fluctuated. From moderately effective, effective to very effective. The causes of fluctuation include entertainment tax deposits not according to the rules, and an online tax payment system is enforced. Recommendations given to increase socialization or counseling about the benefits of tax collection, online payment systems, take firm action by providing fines and sanctions for negligent taxpayers, rescheduling the number of entertainment taxpayers.